The white princess - Gregory, Philippa (New York : Simon & Schuster, 2013)
Passionately in love with Richard III in spite of her arranged marriage to pretender to the throne Henry Tudor, Princess Elizabeth of York is forced to marry the man who murdered her lover and create a royal family under the controlling gaze of his mother, Margaret Beaufort.
"A Touchstone book."
Includes bibliographical references (p. 523-528).
Keywords: Elizabeth, -- Queen, consort of Henry VII, King of England, -- 1465-1503 -- Fiction; Queens -- Great Britain -- Fiction; Great Britain -- History -- Henry VII, 1485-1509 -- Fiction; Great Britain -- History -- Richard III, 1483-1485 -- Fiction; Biographical fiction; Historical fiction